The role of perireceptor events in flavor perception - Boichot, Valentin; Muradova, Mariam; Nivet, Clément; Proskura, Alena; Heydel, Jean-Marie; Canivenc-Lavier, Marie-Chantal; Canon, Francis; Neiers, Fabrice; Schwartz, Mathieu (Frontiers in Food Science and Technology, 2022)
The sensory perception of food is a complex phenomenon involving the integration of different stimuli (aroma, taste, trigeminal sensations, texture and visual). Flavor compounds activate odorant, taste and trigeminal chemoreceptors, generating a depolarization of the sensory neurons and then the consciousness of food flavor perception. Recent studies are increasingly highlighting the importance of perireceptor events, which include all the molecular events surrounding the receptors, in the modulation of flavor perception. These events affect the quantity and quality of flavor compounds in the environment of chemoreceptors. They include the metabolization of flavor compounds by enzymes present in biological fluids (saliva and mucus) and the oronasal epithelia and noncovalent interactions with binding proteins. Perireceptor mechanisms have been extensively studied in insects and mammals, demonstrating the importance of the entailed processes in the termination of the chemical signal. In humans, research is in full swing. Here, we reviewed the perireceptor mechanisms recently reported in vitro, in biological fluids and in cells and in vivo in humans. These studies indicate that perireceptor mechanisms likely have an important contribution to flavor perception. This mini-review focuses on recent pioneering studies that are paving the way for this new research area. It also suggests that new approaches taking into account the real conditions of food consumption will be required in the future to accurately address this question.